Comprehensive Analysis of VOCs in an Industrial Harbor City: Spatiotemporal Distribution, Health Risk, and Potential Sources - Thi-Hieu Le; Chung-Shin Yuan; Chitsan Lin; Zhi-Ping Hsu; I-Hsin Hsu; Lin-Chi Wang (Aerosol and Air Quality Research)
Abstract Volatile organic compounds (VOCs) measurements during the worst air quality season of 2020–2022 were conducted at three distinct sites within Kaohsiung Harbor, Taiwan’s largest harbor and a significant hub in Asia. Air VOCs samples were collected continuously in 24 h by canister and analyzed by GC/MS with pre-concentration systems according to U.S. EPA Method TO-15. The source apportionment was defined by diagnostic ratio analysis and positive matrix factorization (PMF) model while ozone formation potentials (OFP) were estimated by maximum incremental reactivity method. Health risk was estimated by unit risks and reference concentration for cancer and non-cancer risk, respectively. The results indicate a decrease in average total VOC (TVOC) concentrations (ppbv) over the study period: 37.9 ± 4.5 in 2020, 23.3 ± 9.9 in 2021, and 23.3 ± 2.6 in 2022. Dominant VOC components were C2-VOCs and aromatics, which made up more than 50% of TVOCs. According to diagnostic ratio analysis, local anthropogenic emissions, such as industrial and ship/vehicle emissions around harbor area, were main causes. Four sources were identified by positive matrix factorization (PMF), with industrial activities (33.7%), followed by vehicle and ship emissions (30.6%), solvent usages (21.1%), and fuel evaporations (14.6%). OFP results indicated that toluene was primary OFP contributor, accounting for an average of 30.4%, followed by C2-VOCs at 16.2% and m/p-xylenes at 12.5%, collectively contributing nearly 60% to OFP. These OFP contributors were significantly attributed to vehicle/ship emissions and solvent usages. Cumulative non-carcinogenic hazard indices were less than 1 indicates an acceptable non-carcinogenic health concern. Notably, only 1,2-dichloroethane exceeded the threshold of 1.0 × 10-6 for carcinogenic risk throughout the three-year observation period, while 1,3-butadiene indicated a high risk only in 2020. Industrial emissions could mainly contribute to carcinogenic risks in Kaohsiung Harbor and the surrounding area. The results are conducive to developing control strategies for VOC emissions to reduce human exposure risk to ambient air.